Hair cortisol, glucocorticoid gene receptor polymorphisms, stress, and testicular function. (December 2022) - Nordkap, Loa; Almstrup, Kristian; Priskorn, Lærke; Bang, Anne Kirstine; Stalder, Tobias; Petersen, Jørgen Holm; Hansen, Åse Marie; Juul, Anders; Johannsen, Trine Holm; Jørgensen, Niels
Abstract: Objective: Self-reported psychological stress has been associated with decreased semen quality. Cortisol levels in scalp hair (hair cortisol concentration, HCC) has emerged as a potential objective marker of psychological stress. Thus, we investigated if HCC was associated with markers of testicular function. Furthermore, we examined whether three common single nucleotide polymorphisms in the glucocorticoid-receptor gene ( NR3C1, chromosome 5), potentially affecting receptor sensitivity, were associated with HCC and could influence the studied association between HCC and testicular function. Design: Cross-sectional study. Methods: We analysed HCC, serum-levels of reproductive hormones, semen parameters, and the three NR3C1- polymorphisms; Bcl I (rs41423247), Tth111 I (rs10052957), and 9β (rs6198), in a population of 696 men from the general population. Results: HCC was not associated with testicular function, and adjustment for the three NR3C1- polymorphisms did not alter the results. However, HCC increased significantly with the number of Tth111 I minor-alleles (T) and decreased significantly with the number of 9β minor-alleles (G). Conclusion: Given previously shown associations between stress and semen quality, and that no association between HCC and self-reported stress was observed in the current study, we speculate that negative reproductive effects of stress may not be mediated directly by cortisol. This study demonstrates associations between HCC and glucocorticoid receptor gene variants indicating that these SNPs may influence systemic glucocorticoid levels, but the potential health effects of such alterations are yet unknown. Highlights: Psychological stress has been shown to be associated with impaired semen quality. Hair cortisol, a potential stress marker, was not associated with testis function. Adjustment for the Bcl I, Tth111 I, and 9β NR3C1 SNPs did not influence the results. The Tth111 I and the 9β SNPs were associated with hair cortisol.